Plantar ecchymosis/Plantar nevus cell nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Ecchymoses and melanocytic lesions, that in childhood mainly consist of nevic malformations, should be differentiated only in one site, the plantar region. Nevus cell nevi of the plantar region may be congenital or acquired and are usually junctional. Junctional nevi are characterized by nevus cells localized only level with the dermal epidermal junction. This is why they are flat, from a clinical point of view. (...).